Data from: Small Carbonaceous Fossils (SCFs) from North Greenland: new light on metazoan diversity in early Cambrian shelf environments - Wallet, Elise; Slater, Ben; Willman, Sebastian; Peel, John (Zenodo, 2020)
The Sirius Passet Lagerstätte of North Greenland provides one of the oldest records of soft-bodied metazoan-dominated ecosystems from within the early Cambrian. The Lagerstätte site itself is restricted to just a single ~1 km-long outcrop located offshore from the shelf margin, in an area that has been affected by metamorphic alteration during the Ellesmerian Orogeny (Devonian–Early Carboniferous). The recent recovery of Small Carbonaceous Fossils (SCFs) to the south in areas that have escaped the effects of this deformation has substantially expanded the known coverage of organic preservation into shallower-water depositional settings in this region. Here we describe additional SCF assemblages from the siliciclastic shelf succession of the Buen Formation (Cambrian Series 2, Stages 3-4; ∼ 515 Ma), expanding upon the previously documented SCF biota. Newly recovered material reveals a rich diversity of non-mineralizing metazoans, chiefly represented by arthropod remains. These include the filtering and grinding elements of a sophisticated crustacean feeding apparatus - the oldest crustacean remains reported to date - alongside an assortment of bradoriid sclerites, including almost complete, three-dimensional valves which tie-together a number of SCFs previously found in isolation. Other metazoan remains include various trilobite cuticles, diverse scalidophoran sclerites, and a range of metazoan fragments of uncertain affinities. This shallower-water assemblage differs substantially from the Sirius Passet biota, which is dominated by problematic euarthropod stem-group members and sponges. Though some of these discrepancies are attributable to taphonomic or temporal factors, these lateral variations in taxonomic composition also point to significant palaeoenvironmental and/or palaeoecological controls on early Cambrian metazoan communities. The dataset includes a series of folders containing high-resolution images of specimens figured in Wallet et al. (2020), together with two tabular files ...